Designing a New Product Development Model Based on Open Innovation Using the Grounded Theory Approach - Kalantari, Amir Tooraj; Akbari, Mahsa; Makizadeh, Vahid (AI and Tech in Behavioral and Social Sciences, 2024)
Developing new products through open innovation as a strategic approach not only aids organizations in discovering new markets but also facilitates the creation of innovative and valuable products and services. This research aims to propose a new product development model based on open innovation in small and medium-sized enterprises (SMEs). This research employed a qualitative-inductive approach utilizing the Strauss-Corbin grounded theory method. The data collection tool was a semi-structured interview. Using the grounded theory method, data obtained from interviews with 16 managers of SMEs were analyzed through three stages of open, axial, and selective coding. The findings revealed a general category in the form of a paradigm model, which includes causal conditions (financial incentives, competitive advantage, core strategy, market orientation, and customer orientation); core phenomenon (opportunism, organizational resources—both tangible and intangible, process capabilities, product commercialization, and organizational ambivalence); underlying conditions (lack of financial resources for new product development, limited access to modern technology for design, testing, and production, insufficient specialized manpower and technical knowledge, and a scarcity of idea centers in the country compared to other nations); intervening conditions (sanctions and governmental bureaucracies); and strategies (strategic foresight, leveraging network capabilities, centralized marketing, and differentiated marketing). The consequences identified include financial-economic, marketing, and structural outcomes. SMEs are often recognized as critical economic and entrepreneurial components in many countries, playing a significant role in job creation and economic growth. Developing new products through open innovation is a strategic approach that fosters the creation of innovative and valuable products and services by leveraging cooperation and interaction with both internal and external stakeholders of SMEs.